The Influence of DeepL Translator On EFL Students’ Writing - Kirana, Amanda; Kembaren, Farida Repelita Waty; Hz, Benni Ichsanda Rahman (CV. ITTC INDONESIA, 2024)
DeepL Translators are one form of technology that is developing today. The use of technology has a positive impact on the language learning process. Most students make mistakes in writing. DeepL Translator is a translation machine that can be utilised to help with writing. Therefore, a researcher examined the role of DeepL Translator in the language learning process, especially in writing revision. While there have been several studies on machine translation in writing, few have examined the impact of DeepL Translator on the writing of EFL students who use DeepL Translator. A study conducted with second semester English Language Education students at a university in North Sumatra in 2024 involved 27 students as a sample, with four being interviewed about their use of DeepL Translator in their writing revision. The research design used mixed methods with an explanatory sequential strategy. The study included analyses of writing tasks and interviews. Writing tasks were assessed using SPSS 29 with a paired t-test at the 5% significance level, which showed a significant increase in scores <0.001. The interviews, which were then analysed using the Miles and Huberman interactive approach, showed the positive impact of using DeepL Translator. The students reported improved text quality, better errors, and convenience of use. In addition, DeepL Translator also supported students' writing strategies during revision. The students re-examined and utilised prior knowledge while revising their texts. However, they also noted challenges encountered, especially with specialised terms and different contexts than usual. Although DeepL has improved the quality of their writing, careful review of the translations remains important.